Geochemical Characteristics of Rocks in Coal Mines (Case Study of Coal Mining PT. ABC): Karakteristik Geokimia Batuan Pada Tambang Batubara (Studi Kasus Penambangan Batubara PT. ABC) - Gindang Rain Pratama; Diana Irmawati Pradani; Harsalim Aimunandar Jayaputra; Gregorius Aryoko Gautama; Muhammad Tri Aditya; Armin Naibaho (Media Ilmiah Teknik Lingkungan (MITL), 2025)
At the end of mining, an open pit coal mine will form a mine sump, also known as a “pit lake”. At PT ABC, the pit wall rock lithology consists of 30% potentially acidic rock and 70% non-acidic rock, with low pH sump water quality. The static test is intended to calculate the balance of acid-forming and acid-consuming components. The static test does not consider the rate of acid formation and neutralization. The objective is to determine the potential for acid formation to occur in the rock. The kinetic test aims to understand the kinetics of acid formation reactions in samples through a simulation of oxidation reactions in rocks. This test can predict long-term weathering characteristics as a function of time. Of the 4 rock samples tested statically, all samples showed PAF (Potencial Acid Forming) screening criteria. The results of the kinetic test showed that sample S1 experienced an increase in pH to 4,43, sample S2 experienced a decrease in pH to 8,03, sample S3 experienced an increase in pH to 2,44, and sample S4 experienced an increase to 7,24.